Preparation method and application of phycocyanin-fucoxanthin composite nanoparticles
By preparing algae blue protein-glycotium alcoholic composite nanoparticles, the attractiveness of the charging of chilin hybrotic acid is used to solve the problem of poor stability of glycotium and algaein, and realizes its higher stability and biological biology in medicines. active.
Patent Information
- Application Number
- CN202411922590.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-01-28
AI Technical Summary
Fucoctin and phycocyanin are prone to denaturation and inactivated under extreme conditions and have poor stability, which limits their application in medicines.
The preparation method of algae blue protein-kyloglobin composite nanoparticles is used to mix algae blue protein and glycotium alcoholin, and add shell polytyite solution during the mixing process to form a stable composite nanoparticles.
It improves the stability and biological activity of lymalidine and algae blue protein, and enhances its retention rate and functional performance in different environments.
Smart Images

Figure CN119367325A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biotechnology, and specifically relates to a preparation method of phycocyanin-fucoxanthin composite nanoparticles and application thereof. Background Art
[0002] Fucoxanthin (FX) is a fat-soluble natural carotenoid with high polarity and is easily soluble in organic solvents such as methanol, ethanol and chloroform. Fucoxanthin is mainly derived from large brown algae. In addition to playing an important role in photosynthesis and photoprotection, it also has a wide range of biological activities, such as antioxidant, anti-obesity, anti-diabetic and anti-inflammatory, and has important application potential in the treatment and prevention of various cancers and tumors.
[0003] Fucoxanthin is easily decomposed by light and oxygen under normal conditions, and has poor stability. It is easily degraded by heat, and can degrade to varying degrees between 25 and 100°C, and the higher the temperature, the faster the degradation rate. In an oxygen-free environment at room temperature, fucoxanthin will also undergo isomerization when exposed to light of a certain intensity (300 to 2000 lux). Chemical reagents such as strong acids and strong bases can also destroy the structure of fucoxanthin, but its stability will increase under weak acid conditions. In addition, its hydrophobic properties limit the application of fucoxanthin in water-soluble substrates such as beverages and pigments; in addition, fucoxanthin is extremely easy to decompose in the low pH environment of human gastric juice, resulting in incomplete metabolism and absorption in the intestines, hindering the performance of its biological functions and low bioavailability. In summary, the market prospect of fucoxanthin is very broad, but due to its highly unsaturated structure, it has defects such as poor water solubility and strong environmental sensitivity, which greatly limit the actual production and application of fucoxanthin functional drugs. It also confirms the necessity of taking certain protective measures for fucoxanthin to improve its stability and bioavailability.
[0004] Phycocyanin (PC) is a water-soluble protein of light-harvesting pigments. It is insoluble in organic reagents such as alcohol. Its aqueous solution is blue. It can be widely used in food additives, safety dyes, cosmetics and other industries. It can also be used as a functional ingredient in the biomedicine field and has great potential for development as a drug. Phycocyanin has good biological activity, including antioxidant, anti-inflammatory, anti-radiation, and immunomodulatory effects. It is widely used in the food, cosmetics, and pharmaceutical industries. However, similar to fucoxanthin, phycocyanin is easily denatured and inactivated under extreme conditions, and is sensitive and unstable to temperature, light, and pH. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a preparation method and application of phycocyanin-fucoxanthin composite nanoparticles which can simultaneously improve the stability and biological activity of fucoxanthin and phycocyanin.
[0006] The technical solution adopted by the present invention to solve the above technical problems is: a method for preparing phycocyanin-fucoxanthin composite nanoparticles, comprising the following steps: mixing a phycocyanin aqueous solution with a concentration of 2 mg / mL and a fucoxanthin ethanol solution with a concentration of 10 mg / mL in a volume ratio of (200-20):1, stirring at 600-1200 rpm for 20-40 min, adding a chitosan acetic acid solution with a concentration of 0.02-0.1wt% in half the volume of the phycocyanin aqueous solution, and stirring at 600-1200 rpm for 1-3 h to obtain phycocyanin-fucoxanthin composite nanoparticles.
[0007] Furthermore, the preparation method of the phycocyanin aqueous solution is as follows: dissolving phycocyanin in deionized water, stirring it magnetically to completely dissolve it, and obtaining a phycocyanin aqueous solution with a concentration of 2 mg / mL.
[0008] Furthermore, the preparation method of the fucoxanthin ethanol solution is as follows: dissolve fucoxanthin in 95% ethanol, stir it magnetically to completely dissolve it, and obtain a fucoxanthin ethanol solution with a concentration of 10 mg / mL.
[0009] Furthermore, the preparation method of the chitosan acetic acid solution is as follows: dissolving chitosan in an acetic acid aqueous solution with a volume concentration of 1% to obtain a chitosan acetic acid solution with a chitosan concentration of 0.02-0.1wt%.
[0010] Preferably, the volume ratio of the phycocyanin aqueous solution to the fucoxanthin ethanol solution is 50:1.
[0011] Preferably, the concentration of chitosan in the chitosan acetic acid solution is 0.1 wt %.
[0012] The present invention also provides the use of the phycocyanin-fucoxanthin composite nanoparticles in the preparation of drugs for inhibiting inflammation.
[0013] Compared with the prior art, the advantages of the present invention are as follows: the present invention discloses for the first time a preparation method and application of phycocyanin-fucoxanthin composite nanoparticles, which utilizes embedding means to use fucoxanthin as the wall core and phycocyanin as the wall material, utilizes the hydrophobic force of fucoxanthin to load phycocyanin with poor stability, and utilizes the attraction of positive and negative charges based on the properties of phycocyanin with negative charge and chitosan with positive charge, thereby obtaining phycocyanin-fucoxanthin composite nanoparticles, which improves the stability of the two active substances and also improves their biological activity. The method is simple and convenient to operate, low in cost, short in production cycle, and suitable for batch processing and factory production. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1The effect of different mixing volume ratios on the fucoxanthin embedding rate in phycocyanin-fucoxanthin nanoparticles in specific example 2; Figure 2 The effect of different chitosan concentrations on the fucoxanthin embedding rate in phycocyanin-fucoxanthin composite nanoparticles in specific example 2; Figure 3 This is a structural characterization of the phycocyanin-fucoxanthin composite nanoparticles in the specific embodiment 3, wherein a is a UV-visible spectrum, b is a fluorescence spectrum, and c is a circular dichroism spectrum; Figure 4 The stability test results of the phycocyanin-fucoxanthin composite nanoparticles in the specific example 4, wherein a is the effect of the heating time at 60°C on the retention rate of fucoxanthin in different samples, b is the effect of the ultraviolet light irradiation time on the stability of fucoxanthin in different samples; c is the effect of the storage time at room temperature on the retention rate of fucoxanthin in different samples; Figure 5 : are the results of biological activity determination of different samples in specific embodiment 5, wherein a is the nitric oxide content in macrophages after PC sample treatment, b is the nitric oxide content in macrophages after FX sample treatment, and c is the nitric oxide content in macrophages after PC+FX+CS sample treatment. DETAILED DESCRIPTION
[0015] The present invention is further described in detail below with reference to the accompanying drawings.
[0016] Specific example 1: Preparation of phycocyanin-fucoxanthin composite nanoparticles, the steps are as follows: Step 1, dissolve 20 mg of phycocyanin in 10 mL of deionized water, stir with a magnetic stirrer at 800 rpm for 2 h to completely dissolve it, and obtain a phycocyanin aqueous solution with a concentration of 2 mg / mL, recorded as PC; Step 2, dissolve 10 mg of fucoxanthin in 1 mL of 95% ethanol, stir with a magnetic stirrer at 800 rpm for 2 h to completely dissolve it, and obtain a 10 mg / mL fucoxanthin ethanol solution, recorded as FX; Step 3, 4 mL of 2 mg / mL phycocyanin aqueous solution and 20-200 μL of 10 mg / mL fucoxanthin ethanol solution were stirred at 800 rpm for 30 min to obtain a phycocyanin-fucoxanthin nanoparticle solution, which was recorded as PC+FX; Step 4: Add 2 mL of 0.02-0.1 wt% chitosan acetate solution to the phycocyanin-fucoxanthin nanoparticle solution obtained in step 3, and stir at 600-1200 rpm for 1-3 h to obtain phycocyanin-fucoxanthin composite nanoparticles, denoted as PC+FX+CS, wherein the preparation method of the chitosan acetate solution is as follows: dissolve chitosan (abbreviated as CS) in 1% volume concentration of acetic acid aqueous solution to obtain a chitosan acetate solution with a chitosan concentration of 0.02-0.1 wt%.
[0017] Specific Example 2: The optimal formula of the phycocyanin-fucoxanthin composite nanoparticles prepared in Specific Example 1 is determined.
[0018] Determination of embedding rate: The phycocyanin-fucoxanthin composite nanoparticle solution was subjected to rotary evaporation to remove ethanol, and the volume of ethanol removed was supplemented with the same volume of distilled water. After sufficient stirring, the supernatant was taken after centrifugation at 10,000 g for 20 min, and a reagent composed of ethanol and n-hexane in a volume ratio of 1:2 with a volume of 6 times the supernatant was added. After mixing evenly, the solution was centrifuged again at 10,000 g for 20 min, and the supernatant was taken and measured with an ultraviolet spectrophotometer. According to the relationship between the absorbance value and the fucoxanthin concentration, the fucoxanthin concentration in the supernatant was calculated, and the fucoxanthin embedding rate was further calculated. The calculation formula is as follows: embedding rate (%) = (total amount of fucoxanthin - amount of fucoxanthin in supernatant) / total amount of fucoxanthin * 100, unit μg.
[0019] Figure 1 The embedding efficiency was measured after 4 mL of phycocyanin aqueous solution reacted with 20 μL, 30 μL, 40 μL, 80 μL, 120 μL, 160 μL, and 200 μL of fucoxanthin ethanol solution (corresponding volume ratios of 200:1, 400:3, 100:1, 50:1, 100:3, 25:1, and 20:1). The results showed that when the volume ratio of the phycocyanin aqueous solution to the fucoxanthin ethanol solution was 200:1, the embedding efficiency was 84.37±3.35%, and when the volume ratio of the phycocyanin aqueous solution to the fucoxanthin ethanol solution was 50:1, the embedding efficiency could reach 95.61±0.54%. However, when the fucoxanthin concentration was too high, flocculation would occur in the phycocyanin-fucoxanthin composite nanoparticle solution. Therefore, a volume ratio of 50:1 between the phycocyanin aqueous solution and the fucoxanthin ethanol solution was selected as the optimal ratio for subsequent experiments.
[0020] After 4 mL of 2 mg / mL phycocyanin aqueous solution and 80 μL of 10 mg / mL fucoxanthin ethanol solution were stirred at 800 rpm for 30 min, different concentrations of chitosan acetic acid solution were added to obtain phycocyanin-fucoxanthin composite nanoparticle solutions, and the fucoxanthin encapsulation rate was measured. Figure 2 As shown in the figure, except for the addition of 0.005wt% and 0.05wt% chitosan acetate solution, the fucoxanthin embedding rates of the other phycocyanin-fucoxanthin composite nanoparticles can reach more than 90%, especially when the concentration of chitosan acetate solution is 0.1wt%, the embedding rate can reach 94±1.39%. Therefore, 0.1wt% chitosan acetate solution was selected as the optimal ratio for subsequent experiments.
[0021] Specific Example 3: Structural characterization of the phycocyanin-fucoxanthin composite nanoparticles prepared in Specific Example 1.
[0022] 1. UV-visible absorption spectrum determination: Use a UV spectrometer to analyze the UV-visible absorption spectrum of phycocyanin-fucoxanthin composite nanoparticles. Dilute the measured sample with deionized water to an absorbance A of 0.5 to 1. Set the absorption wavelength to 450nm and measure the absorbance of phycocyanin and fucoxanthin at this wavelength.
[0023] Figure 3 a is the UV-visible spectrum of PC and FX samples at 200-700 nm. Figure 2 As shown in Figure a, PC has absorption peaks at both 275 nm and 618 nm. The peak at 275 nm is attributed to the π→π* electronic transition of the aromatic residue. The maximum absorption peak of PC at 618 nm indicates the presence of a tetrapyrrole ring in PC. FX has an obvious absorption peak at 450 nm, indicating that fucoxanthin has the strongest light absorption ability at 450 nm.
[0024] 2. Fluorescence spectrum measurement: The fluorescence of phycocyanin-fucoxanthin composite nanoparticles was analyzed using a fluorescence spectrophotometer. The sample to be measured was diluted with deionized water to an absorbance A of 0.5-1, the excitation wavelength was set to 280 nm, the acquisition wavelength range was 290-450 nm, and the scanning speed was 100 nm / min.
[0025] Fluorescence spectroscopy can be used to evaluate the mechanism of interaction between proteins and small molecules. Figure 3 Figure b shows the fluorescence spectra of PC and PC+FX at an excitation wavelength of 280 nm. At an excitation wavelength of 280 nm, the maximum emission wavelength of PC is 340 nm, which is related to the tryptophan residues in PC. As the FX content increases, the fluorescence intensity of PC gradually decreases, indicating that the fluorescent groups in PC are covered and FX quenches the fluorescence of PC, indicating that fucoxanthin is successfully encapsulated by phycocyanin.
[0026] 3. Circular dichroism spectroscopy determination: phycocyanin and phycocyanin-fucoxanthin composite nanoparticles were subjected to circular dichroism spectroscopy scanning at 20°C with a wavelength range of 190-260 nm, a bandwidth of 1 nm, and a data point sampling time of 0.5 s. Figure 3 Figure c shows the circular dichroism spectra of PC and PC+FX. The spectra show that phycocyanin has two characteristic negative peaks at 208 nm and 222 nm, indicating that phycocyanin contains a high α-helix. After adding fucoxanthin and chitosan, the α-helix content of phycocyanin changes, which indicates that the interaction between fucoxanthin and phycocyanin and chitosan changes the spatial structure of phycocyanin.
[0027] Specific Example 4: Determination of the stability of the phycocyanin-fucoxanthin composite nanoparticles prepared in Specific Example 1.
[0028] 1. Thermal stability determination: Place FX, FX+PC, and FX+PC+CS samples in a light-proof glass vial and heat them in a 60°C water bath for 30, 60, 90, 120, 150, and 180 minutes. Then use a UV-visible spectrophotometer to determine the absorbance A of the above solution at 450 nm and calculate the content of fucoxanthin. The retention rate calculation formula is as follows: Retention rate (%) = fucoxanthin content in samples at different treatment time points / original fucoxanthin content in untreated samples.
[0029] Figure 4 a is the effect of heating time at 60°C on the stability of fucoxanthin in different samples. The results show that after heating at 60°C for 180 min, the retention rate of free FX dropped to 30.15±4.1%, while the retention rate of fucoxanthin in PC+FX was 71.41±4.91%, indicating that the presence of PC enhanced the thermal stability of FX. The retention rate of fucoxanthin in the FX+PC+CS sample was higher than that in the PC+FX sample, indicating that the addition of CS can enhance the retention rate of FX.
[0030] 2. Photochemical stability determination: FX, PC+FX, PC+FX+CS samples were placed under 15 W, 352 nm ultraviolet light for 6 h, 1 ml of sample was taken every 1 h, and after appropriate dilution with ethanol, the absorbance A was measured at 450 nm using a UV-visible spectrophotometer to calculate the fucoxanthin content. The retention rate calculation formula is as follows: Retention rate (%) = fucoxanthin content in samples at different treatment time points / original fucoxanthin content in untreated samples.
[0031] Figure 4Figure b shows the effect of UV irradiation time on the stability of fucoxanthin in different samples. The results show that after 6 h of UV irradiation, the retention rate of free FX was 34.05±0.79%. After 6 h of UV irradiation, the retention rate of FX in PC+FX can be maintained at 65.64%±2.53%. After 6 h of UV irradiation, the retention rate of FX in FX+PC+CS sample can be maintained at 78.15%±1.12%. This indicates that phycocyanin-fucoxanthin composite nanoparticles can avoid the destruction of fucoxanthin under ultraviolet irradiation and improve the retention rate of fucoxanthin.
[0032] 3. Room temperature stability determination: FX, FX+PC, FX+PC+CS samples were placed in light-proof glass vials and stored at room temperature for 3, 6, 9, and 12 days, respectively. The absorbance of the above solutions at 450 nm was then determined using a UV-visible spectrophotometer to calculate the fucoxanthin content. The retention rate calculation formula is as follows: Retention rate (%) = fucoxanthin content in samples at different treatment time points / original fucoxanthin content in untreated samples.
[0033] Figure 4 Figure c shows the effect of storage time at room temperature on the retention rate of fucoxanthin in different samples. The results show that after 12 days of storage at room temperature, the retention rate of free FX was 21.36±0.12%, and the FX retention rate of PC+FX could be maintained at more than 70%. The FX retention rate of FX+PC+CS could be maintained at around 80%. The above results show that PC can prevent FX from being destroyed under high temperature and ultraviolet irradiation and improve the storage stability of FX, while the addition of CS can further enhance the retention rate of FX.
[0034] Specific Example 5: Determination of the biological activity of the phycocyanin-fucoxanthin composite nanoparticles prepared in Specific Example 1.
[0035] Cell sample preparation: RAW264.7 macrophages were cultured at 5*10 5 / mL were inoculated into 96-well culture plates. After culturing for 24 hours, different concentrations of PC, different concentrations of FX and different concentrations of FX+PC+CS samples were added and cultured for 12 hours. Then, lipopolysaccharide was added to make the final concentration of 1μg / mL and cultured for 12 hours as the drug group. At the same time, lipopolysaccharide was added to the blank group to make the final concentration of 1μg / mL and cultured for 12 hours as the positive control group (LPS group), and a blank control group (control) was set up.
[0036] Carbon monoxide content determination: Take cell samples and detect the content of nitric oxide (NO) in RAW264.7 cells according to the requirements of the Bio-Tech Biochemical Kit. Calculate the concentration of nitric oxide in the sample based on the standard curve. Increased NO content in cells is also a manifestation of inflammation, caused by Figure 5 Middle a, Figure 5Medium b and Figure 5 As shown in Figure c, the NO level in LPS-treated cells was significantly higher than that in the blank control group, and as the concentration of FX, FX+PC, and FX+PC+CS samples increased, the NO content also decreased compared with the LPS group. It is worth noting that after adding PC samples, FX samples, and PC+FX+CS samples for treatment, the inflammatory factor NO was significantly reduced compared with the LPS group, especially the PC+FX+CS group was lower than the PC group and FX group alone, indicating that PC+FX+CS has a good inhibitory effect on inflammation.
[0037] The above description is not intended to limit the present invention, and the present invention is not limited to the above examples. Any changes, modifications, additions or substitutions made by a person skilled in the art within the spirit and scope of the present invention shall also fall within the protection scope of the present invention.
Claims
1. A method for preparing phycocyanin-fucoxanthin composite nanoparticles, characterized in that The method comprises the following steps: mixing a phycocyanin aqueous solution with a concentration of 2 mg / mL and a fucoxanthin ethanol solution with a concentration of 10 mg / mL at a volume ratio of (200-20):1, stirring at 600-1200 rpm for 20-40 min, adding a chitosan acetic acid solution with a concentration of 0.02-0.1 wt% which is half the volume of the phycocyanin aqueous solution, and stirring at 600-1200 rpm for 1-3 h to obtain phycocyanin-fucoxanthin composite nanoparticles.
2. The method for preparing phycocyanin-fucoxanthin composite nanoparticles according to claim 1, characterized in that The preparation method of the phycocyanin aqueous solution is as follows: dissolving the phycocyanin in deionized water, stirring it magnetically to completely dissolve it, and obtaining a phycocyanin aqueous solution with a concentration of 2 mg / mL.
3. The method for preparing phycocyanin-fucoxanthin composite nanoparticles according to claim 1, characterized in that The preparation method of the fucoxanthin ethanol solution is as follows: dissolve fucoxanthin in 95% ethanol, stir it magnetically to completely dissolve it, and obtain a fucoxanthin ethanol solution with a concentration of 10 mg / mL.
4. The method for preparing phycocyanin-fucoxanthin composite nanoparticles according to claim 1, characterized in that: The preparation method of the chitosan acetic acid solution is as follows: dissolving chitosan in an acetic acid aqueous solution with a volume concentration of 1% to obtain a chitosan acetic acid solution with a chitosan concentration of 0.02-0.1wt%.
5. A method for preparing phycocyanin-fucoxanthin composite nanoparticles according to any one of claims 1 to 4, characterized in that: The volume ratio of the phycocyanin aqueous solution to the fucoxanthin ethanol solution is 50:
1.
6. The method for preparing phycocyanin-fucoxanthin composite nanoparticles according to claim 5, characterized in that: The concentration of chitosan in the chitosan acetic acid solution is 0.1wt%.
7. Use of phycocyanin-fucoxanthin composite nanoparticles prepared by the method of claim 6 in the preparation of drugs for inhibiting inflammation.
Citation Information
Patent Citations
Zein peptide fucoxanthin nanometer embedding method and obtained product
CN115474694A
Immune adjuvant-loaded phycocyanin nano system as well as preparation method and application thereof
CN116212016A
Acid-modified phycocyanin / carboxylated chitosan compound and preparation method thereof
CN117402414A
Chitosan-coated fucoxanthin fine powder based on casein and method for manufacturing the same
KR1020180050027A
A NANO in micro formulation and process thereof
WO2023187831A1
Cited By
Method for improving the lipid-based dispersibility of phycocyanin and modified phycocyanin
CN122701843A